How to Mitigate the Hard Problem by Adopting the Dual Theory of Phenomenal Consciousness - Polák, Michal; Marvan, Tomáš (Frontiers in Psychology, 2019)
In this paper we propose the following hypothesis: the hard problem of consciousness is in part an artifact of what we call the unitary approach to phenomenal consciousness. The defining mark of the unitary approach is that it views consciousness and phenomenality as inseparable. Giving up this conceptual commitment redefines, in a productive way, the explanatory tasks of the theory of consciousness. Adopting a non-unitary conception of experience does not make the hard problem of consciousness go away completely but it shifts the locus of where the explanation of experience gets really difficult, and cuts down the mystery of consciousness to size. Other advantages of the non-unitary account of consciousness are sketched as well.